Measurement of CP observables for the decays B-+/-->(DCPK)-K-0*(+/-) - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; Pappagallo, M; et al. (2005)
Using a sample of 232×106 Υ(4S)→BB̄ events collected with the BABAR detector at the PEP-II B Factory in 1999-2004, we study B-→D0K*(892)- decays where K*-→KS0π- and D0→K-π+, K-π+π0, K-π+π+π- (non-CP final states); K+K-, π+π- (CP+ eigenstates); KS0π0, KS0, and KS0ω (CP- eigenstates). We measure four observables that are sensitive to the angle γ of the CKM unitarity triangle; the partial-rate charge asymmetries ACP± and the ratios of the B-decay branching fraction in CP± and non-CP decays RCP±: ACP+=-0.08±0.19(stat)±0.08(syst), ACP-=-0.26±0.40(stat)±0.12(syst), RCP+=1.96±0.40(stat) ±0.11(syst), and RCP-=0.65±0.26(stat)±0.08(syst). © 2005 The American Physical Society.